Development and Storage Stability of Cookies from Whole Wheat, Sweet Potato and Mucuna utilis, Composite Flour - , Roseline Nwabugo Attaugwu; , Josephat Ikechukwu Anyadioha; , Kachi Jude Chukwuma (Archives of Current Research International, 2023)
Aim: This study evaluated the effect of storage conditions at ambient (28 ± 2°C) and refrigeration temperature (4 ± 2°C) on the physicochemical properties of Cookies made from Composite flours in the ratio of 50: 30: 20; 50:20:30 (whole wheat, sweet potato flour or Mucuna utilis respectively). Methodology: Flours were obtained from whole wheat (W), peeled and sun-dried potato (S), and boiled oven-dried mucuna (BM) and toasted oven-dried mucuna (TM) bean seed. Cookies made from 100 % whole wheat flour served as control. The physicochemical properties of the cookies were evaluated using standard methods and the data obtained were statistically analyzed. Results and Discussion: The results showed an increase in protein (8.17 % - 18.84 %), crude fiber (1.57 – 7.38 %), and fats (8.81- 14.59 %.). The vitamin values decreased in all the samples after storage except vitamin E (1.05 – 1.87 mg/100 g (before storage) and vitamin E (1.08 -1.92) which remained unaffected after the storage period. After 30 days of storage, the percentage free fatty acid (FFA) values ranged from (0.39 – 0.56 % for samples stored under refrigerated conditions as against 0.58- 0.79 % observed in ambient temperature storage. The Peroxide value showed a slight increase in refrigerated samples (3.9 – 6.98 meq O2/kg) as against that of ambient temperature storage which had higher values (8.22 -12.58 meq O2/Kg). Conclusion: The FFA and peroxide values of samples W50 S30 BM20 and W50 S20 BM30 were within acceptable limit under refrigerated condition indicating that boiling treatment is better preferred than toasting. The study indicated that refrigerated storage is a more suitable storage condition than ambient storage.